"Walk the line": An ethnographic study of the ritual of crossing the Arctic Circle—Case Rovaniemi. (December 2019) - Varnajot, Alix
The Arctic Circle is the most commonly used border to delimit the Arctic region, and has been used in this way to such an extent that across the circumpolar North, municipalities and local communities have built various types of signs, shops and tourist centers for its celebration. This is especially the case in Rovaniemi, Finland, with the creation of the Santa Claus Village, "right" on the Arctic Circle, leading to several thousands of tourists crossing the magical line every year. This article focuses on tourists' practices around Arctic Circle landmarks in Rovaniemi. This study acknowledges the hegemony of the selfie era that is indubitably linked to what is referred to in this article as "border-crossing postures", pertaining to the ritual of performing specific practices, actions and postures that suggest the crossing of a borderline. However, it is argued that in the case of the Arctic Circle in Rovaniemi, these specific postures come from the physical aspect of the landmarks, rather than the tourists recognizing the Arctic Circle as a border.